Role of Decision Making in Supply Chain Management in Accordance with Information and Communication Technologies - Poh, Siew Phung; Raju, Valliappan (International Journal of Supply Chain Management, 2019)
This research paper flags for displaying the fundamental issues concerning the Reverse Supply Chains (RSC) and the explicit characteristics of Decision Support Systems (DSS) intended to be utilized in the RSC the board exercises in accordance with the new Information and Communication Technologies (ICT). Having checked on a few fundamental achievements of the path to the cognizant natural assembling frameworks, Reverse Supply Chain systems, design and exercises are portrayed. Activities and usage arrangements of Decision Support Systems for RSC in some European nations are additionally exhibited. In the last part, the job of pacing innovations to help green assembling advancement with primary accentuation on issues, for example, operator advances, distributed computing, huge information and digital physical frameworks is clarified.